2022
DOI: 10.3928/01477447-20220907-05
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Orthopedic Patients on Medical Cannabis: A Survey of More Than 2500 Patients

Abstract: Nationwide perspectives on cannabis have changed dramatically over recent decades. Although cannabis remains illegal at the federal level, medical cannabis (MC) is now legal in most states, and research has continued to show its effectiveness in a variety of medical conditions. However, both perception and acceptance of MC by the general public are evolving and remain poorly understood. Treating patients effectively with these novel therapeutics requires an understanding of the complex interplay of social and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Regarding the legal aspects of medical cannabis use, our study revealed that a significant majority of patients (90.9%) believe that the law permits the utilization and potential misuse of Cannabis sativa L., notwithstanding the acknowledged risks associated with its consumption. This finding aligns with a study involving American patients, where a majority was aware of the legal status of medical cannabis [ 20 ]. Despite the legal authorization for the use of cannabis-based medicinal products (CBMP), concerns persist regarding illegal access to these products and their quality.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding the legal aspects of medical cannabis use, our study revealed that a significant majority of patients (90.9%) believe that the law permits the utilization and potential misuse of Cannabis sativa L., notwithstanding the acknowledged risks associated with its consumption. This finding aligns with a study involving American patients, where a majority was aware of the legal status of medical cannabis [ 20 ]. Despite the legal authorization for the use of cannabis-based medicinal products (CBMP), concerns persist regarding illegal access to these products and their quality.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, there are significant differences in accessing information about medical cannabis [ 31 ]. Our findings highlight the self-reported use of cannabis, which aligns with a study conducted on Canadian patients who reported a high prevalence of cannabis use as a substitute for other medications such as opioids, benzodiazepines, and antidepressants [ 20 ]. Similarly, a study in Germany revealed that most patients acquire knowledge about medical cannabis through the Internet rather than from physicians [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations